2019
DOI: 10.12691/jfnr-7-9-10
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Healthy Food: How Consumer’s Values Influence the Perceived Healthiness of a Food Product

Abstract: The healthy lifestyle trend represents an opportunity to food manufacturers to redesign their marketing strategy for healthy food products. The prevalent strategy of posting nutritional information may not be effective because consumers use general heuristic cues to infer how healthy is a product. The purpose of this study is to extend the comprehension of the healthy food concept from a consumer perspective by assuming values are the basis to conceptualize healthy food. A qualitative approach was applied to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Finally, we defined the concept of healthiness according to Dagevos and van Ophem's (2013) classification of food consumption values—which are closely related to health benefits—namely product, process, location and emotional values. We added physical well‐being to this conceptualization, given its relationship with the overall concept of long‐term health (Liñán et al, 2019). We present all these concepts and dimensions (which represent the sub‐signals) visually in Figure 1, which includes our proposed conceptual framework and we describe them further in Appendix .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we defined the concept of healthiness according to Dagevos and van Ophem's (2013) classification of food consumption values—which are closely related to health benefits—namely product, process, location and emotional values. We added physical well‐being to this conceptualization, given its relationship with the overall concept of long‐term health (Liñán et al, 2019). We present all these concepts and dimensions (which represent the sub‐signals) visually in Figure 1, which includes our proposed conceptual framework and we describe them further in Appendix .…”
Section: Methodsmentioning
confidence: 99%
“…Consumers perceive typical–local foods to be simple, basic, pure products, and the term “local” is often associated with attributes such as “artisanal,” “biodiversity,” “natural,” “seasonal,” and “nutritious”: all attributes considered to deliver health benefits (Dagevos & van Ophem, 2013; Delind, 2006; La Trobe, 2001). Liñán et al (2019: 684) attributed healthiness to local foods, since their consumption helps to ‘maintain a healthy lifestyle and quality of life for oneself and close relatives'. Moreover, thanks to the proximity of typical–local foods, transport time is shortened, with positive benefits: for example, in the case of fish, it allows optimal maturation and reduced use of preservatives (Birch et al, 2012).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Adopting the consumer-centered framework of Dagevos and van Ophem [16], Liñán, Arroyo, and Carrete [18] applied a qualitative thematic approach to uncover that consumers' conceptualization of good food is tricky, imprecise, and instinctive. The authors further suggested that consumers use utilitarian qualities, such as product and process values, to evaluate how good the food is.…”
Section: Main Results Of the Papersmentioning
confidence: 99%
“…In any case, the location value and emotional values additionally impact the food inclinations of consumers. Unlike Liñán et al [18], who grounded their qualitative approach in a consumer-centered framework, Beavers, Atkinson, and Alaimo [19] focused on a group of vegetable gardeners to discuss what values influenced their decision to harvest more vegetables from their gardens rather than purchase them from the grocery store. The majority of the gardeners noted the freshness and taste of the vegetables they grew through organic cultivation (reflecting values such as environmentally friendly and naturalness), coupled with their desire to adopt the culture of vegetable gardening and avoid wasting vegetables, led to an increased intake of harvested vegetables.…”
Section: Main Results Of the Papersmentioning
confidence: 99%
“…However, other food values, such as health, environmental impact, and ethical concerns, now influence consumer decisions. Due to these influences, increasing interest in unconventional proteins (including plant and insect proteins) is expected in the coming years [ 16 ].…”
Section: Introductionmentioning
confidence: 99%